ANALISIS FAKTOR YANG MEMBENTUK KINERJA (CAMELS) PADA PERBANKAN INDONESIA (Studi Empiris pada Perbankan yang Terdaftar di BEI Periode 2009-2012) - Mega Tiara Cecaria; Wahyu Meiranto (Diponegoro Journal of Accounting, 2015)
This study aimed to examine the factors that form the performance of the banks in Indonesia using CAMELS method. This study also aimed to determine the major factors that form the performance of the banks in Indonesia. The population in this study are all banking companies listed on the Stock Exchange in 2009-2012. The research used quantitative approach with the total number of samples were 116 research samples. However, there were 17 samples were classified as outliers and should be abolished and the number of samples become 99 samples. Company data used for this study is financial ratio that according to CAMELS ratio, consisting of PR, RAR, CAR and DRR as Capital aspects, RORA, AUR, APB and NPL as Assets aspects, LEV, CDR, SPRD, and DEBT as Management aspects, GPM, PM, ROE, ROTA, ROA, GOTA, NPM, NIM, and BOPO as Earning aspect, CASH, QUICK, LDR and ALR as Liquidity aspects, and IER as Sensitivity to Market Risk aspect. The sampling method was purposive sampling of 29 public listed companies and have no delisted during the period of research. Techniques of analysis in this study is using factor analysis. The result indicated that from 26 ratio, there are 2 insignificant ratio as forming the ratio of bank performance, which are LEV & BOPO, and Earning aspect is the major factor that form the performance of the banks using CAMELS method.